Pengaruh Lingkungan Kerja, Kepemimpinan, dan Disiplin Kerja terhadap Prestasi Kerja Pegawai Sekretariat Daerah Kabupaten Empat Lawang - Nyayu Khairani Putri; Dian Septianti; Azzahra, Fatimah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim was carried out by the author with the aim of knowing and analyzing the influence of the work environment, leadership, and work discipline on the work performance of the employees of the Regional Secretariat of Empat Lawang Regency either partially or simultaneously. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, coefficient of determination, partial test and simultaneous test. The population in this study were all employees of the Regional Secretariat of Empat Lawang Regency, totaling 59 people. The results of the analysis and discussion obtained that the work environment has a significant effect on the work performance of the Regional Secretariat of Empat Lawang Regency employees. Leadership has a significant effect on the work performance of the Regional Secretariat of Empat Lawang Regency employees. Work discipline has a significant effect on the work performance of the Regional Secretariat of Empat Lawang Regency employees. The work environment, leadership, and work discipline have a significant effect on the work performance of the employees of the Regional Secretariat of Empat Lawang Regency.